Measuring the Impacts of Extra-Musical Elements in Guitar Music Playing: A Pilot Study - Héroux, Isabelle; Giraldo, Sergio; Ramírez, Rafael; Dubé, Francis; Creech, Andrea; Thouin-Poppe, Louis-Édouard (Frontiers in Psychology, 2020)
Philosophers, composers, and musicians have long argued whether instrumental music finds meaning in its formal structure and musical content (Hanslick, 1986) or through reference to extra-musical elements, like narratives, emotions or memories. (Meyers, 1956). While the use of extra-musical elements appears grounded in individual musicians’ priorities for performance and teaching (Héroux, 2018), the impact of emotional indications on expressivity has not previously been studied in a large-scale experiment. The aim of these two pilot studies was to construct the methodology for a larger project to study the impact of the use of extra-musical elements on the sound results of guitarists. We asked guitar students to record one short newly composed piece, Evocation 1according to the following conditions: A) in a non-expressive manner, B) according to the notated musical indications, and C) with the addition of suggested contextual and emotional extra-musical elements to the musical instructions. We asked two expert guitarists to evaluate the level of expressiveness for conditions B and C and conducted interviews with participants to collect data on the experimental process to refine protocol. To more objectively measure manifestations of objectivity from the recorded performances, we extracted data from each recording about pitch, dynamics and timing, as well as expressive dynamic deviations. The impact of both recording conditions and the expertise level of performers on the quality of this audio data led us to change the analysis design from a comparative design (with other subject) to a self-comparative design (each subject with himself) for the larger study.